Ceramics in transition : production and exchange of late Byzantine-early Islamic pottery in Southern Transjordan and the Negev - Holmqvist, Elisabeth, (Archaeopress Publishing Ltd., 2019)
This volume focuses on the utilitarian ceramic traditions during the socio-political transition from the late Byzantine into the early Islamic Umayyad and 'Abbasid periods, in southern Transjordan and the Negev. Production clusters, manufacturing techniques, distribution patterns, and material links between communities are analysed.